Interface‐Induced Electrocatalytic Enhancement of CO2‐to‐Formate Conversion on Heterostructured Bismuth‐Based Catalysts - Sui, Peng‐Fei; Xu, Chenyu; Zhu, Meng‐Nan; Liu, Subiao; Liu, Qingxia; Luo, Jing‐Li (Small (Weinheim an der Bergstrasse, Germany), 2022)
Electrochemical CO2 reduction reaction (CO2RR) is a promising approach to convert CO2 to carbon‐neutral fuels using external electric powers. Here, the Bi2S3‐Bi2O3 nanosheets possessing substantial interface being exposed between the connection of Bi2S3 and Bi2O3 are prepared and subsequently demonstrate to improve CO2RR performance. The electrocatalyst shows formate Faradaic efficiency (FE) of over 90% in a wide potential window. A high partial current density of about 200 mA cm−2 at −1.1 V and an ultralow onset potential with formate FE of 90% are achieved in a flow cell. The excellent electrocatalytic activity is attributed to the fast‐interfacial charge transfer induced by the electronic interaction at the interface, the increased number of active sites, and the improved CO2 adsorption ability. These collectively contribute to the faster reaction kinetics and improved selectivity and consequently, guarantee the superb CO2RR performance. This study provides an appealing strategy for the rational design of electrocatalysts to enhance catalytic performance by improving the charge transfer ability through constructing a functional heterostructure, which enables interface engineering toward more efficient CO2RR. The heterostructured Bi2S3‐Bi2O3 nanosheets with substantial amount of interface are designed, which demonstrate the enhanced CO2 electroreduction performance. The fast‐interfacial charge transfer induced by the electronic interaction at the interface, together with the increased number of active sites and the improved CO2 adsorption ability, collectively contribute to the improved electrocatalytic performance.